Ligand promoted and controlled palladium-catalyzed intramolecular Heck reaction of homoallyl alcohols: a facile synthesis of cyclopentaannulated quinolines - Singh, Radhey M.; Chandra, Atish; Sharma, Neha; Singh, Bhawana; Kumar, Ritush (Tetrahedron, 2012)
Bidentate phosphine ligands in palladium-catalyzed intramolecular Heck reactions of 2-chloroquinolin-3-yl-(1-homoallyl)alcohols are described to afford facile synthesis of 3-methylene-2,3-dihydro-1H-cy-clopenta[b]quinolines in improved yields. We further observed using bulky aromatic phosphine ligand in Pd-catalyzed intermolecular Heck coupling reaction at olefinic centers with iodobenzene also favored exclusively Heck products in excellent yield. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Heck cyclization; Homoallyl alcohol; Ligand promoted; Palladium-catalyzed; Quinoline

CO2 Laser direct written MOF-based metal-decorated and heteroatom-doped porous graphene for flexible all-solid-state microsupercapacitor with extremely high cycling stability - Basu, Aniruddha; Roy, Kingshuk; Sharma, Neha; Nandi, Shyamapada; Vaidhyanathan, Ramanathan; Rane, Sunit; Rode, Chandrashekhar V.; Ogale, Satishchandra B. (ACS Applied Materials & Interfaces, 2016)
Over the past decade, flexible and wearable microelectronic devices and systems have gained significant importance. Because portable power source is an essential need of such wearable devices, currently there is considerable research emphasis on the development of planar interdigitated micro energy-torage devices by employing diverse precursor materials to obtain functional materials (functional carbon, oxides, etc.) with the desirable set of properties. Herein we report for the first time the use of metal organic framework (MOF) and zeolitic imidazolate framework (ZIF-67) for high-wavelength photothermal laser direct writing of metal-decorated, heteroatom-doped, porous few-layer graphene electrodes for microsupercapacitor application. We argue that the specific attributes of MOF as a precursor and the high-wavelength laser writing approach (which creates extremely high localized and transient temperature (>2500 degrees C) due to strong absorption by lattice vibrations) are together responsible for the peculiar interesting properties of the carbon material thus synthesized, thereby rendering extremely high cycling stability to the corresponding microsupercapacitor device. Our device exhibits near 100% retention after 200 000 cycles as well as stability under 150 degrees bending.

Nanotubular hard carbon derived from renewable natural seed gel for high performance sodium-ion battery anode - Sharma, Neha; Gawli, Yogesh; Ahmad, Absar; Muhammed, Musthafa; Ogale, Satishchandra (Chemistryselect, 2017)
Electrical energy storage devices such as batteries and supercapacitors are perhaps the most researched topic today in view of its critical implications for the successful implementations of various renewable energy harvesting initiatives. Amongst the various battery systems being currently examined, the Li-battery continues to be a main player, but the Na-ion battery has been attracting significant attention lately due to the concerns about the limited reserves and high cost of Li. Hard carbon is recognized to be a good anode material for Na-battery. In this work we present a novel approach to synthesize such hard carbon from a natural gel derived from the commonly used Basil seeds (Osimum Basilicum) which swell 30 times their weight by absorbing water. The hard carbon obtained by pyrolysis of the freeze-dried mucilage possesses sheet-like and tubular morphology with decorated surface defects attributed to the presence of oxygen functionalities. This hard carbon shows a good reversible capacity of 195 mAh g(-1) at 0.1A g(-1) with an impressive approximate to 91% retention of initial capacity after 300 cycles and sustains high current densities with not much change in capacity value.

Electrochemical evaluation of the stability and capacity of r-GO-wrapped copper antimony chalcogenide anode for Li-ion battery - Yadav, Poonam; Sharma, Neha; Patrike, Apurva; Sabri, Ylias M.; Jones, Lathe A.; Shelke, V. Manjusha (ChemElectroChem, 2020)
Poor cycling stability and capacity fade are primary concerns for next-generation anode materials for Li-ion batteries. In non-carbonaceous anode materials, alloying with Li leads to volume increase that affects practical applications, and increase in particle size, amorphization and reduced conductivity can all lead to a loss of performance. In this work, binary antimony sulfide (Sb2S3) and ternary copper antimony sulfide (CuSbS2) are synthesized by a convenient solvothermal process. These materials are used to study the Li-active/inactive concept, by incorporating Cu into Sb(2)S(3)forming CuSbS(2)wherein Cu is Li inactive whereas Sb is Li active. By direct comparison, we have shown that incorporating Cu into binary antimony sulfide (Sb2S3) resulting into ternary copper antimony sulfide (CuSbS2) addresses the problem of poor conductivity and capacity loss, as Cu provides conductivity leading to enhanced charge transfer and prevents Sb particle aggregation while charge-discharge by exhibiting spectator or diluent ion effect. The better performance of CuSbS(2)is associated with the better Li(+)ion diffusion in the CuSbS2(D=8.97x10(-15) cm(2) s(-1)) compared to Sb2S3(D=2.76x10(-15) cm(2) s(-1)) and lower series resistance of CuSbS2(R=4.70x10(5) omega) compared to Sb2S3(R=5.81x10(8) omega). We have also investigated the composite with the addition of rGO. The CuSbS2-rGO delivered a reversible capacity of 672 mAh g(-1)after 1000 cycles at 200 mA g(-1)which has shown best performance.
Keywords: Batteries; chalcogenides; Diffusion coefficient; lithium; Ternary sulfides